2018
DOI: 10.1038/s41467-018-05555-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic microbe communities provide internal reference standards for metagenome sequencing and analysis

Abstract: The complexity of microbial communities, combined with technical biases in next-generation sequencing, pose a challenge to metagenomic analysis. Here, we develop a set of internal DNA standards, termed “sequins” (sequencing spike-ins), that together constitute a synthetic community of artificial microbial genomes. Sequins are added to environmental DNA samples prior to library preparation, and undergo concurrent sequencing with the accompanying sample. We validate the performance of sequins by comparison to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 57 publications
1
115
0
Order By: Relevance
“…"A method for simultaneous measurement of soil bacterial abundances and community composition via 16S rRNA gene sequencing". Hardwick et al (2018). "Synthetic microbe communities provide internal reference standards for metagenome sequencing and analysis".…”
Section: Design (Taxon or Sequence)mentioning
confidence: 99%
See 1 more Smart Citation
“…"A method for simultaneous measurement of soil bacterial abundances and community composition via 16S rRNA gene sequencing". Hardwick et al (2018). "Synthetic microbe communities provide internal reference standards for metagenome sequencing and analysis".…”
Section: Design (Taxon or Sequence)mentioning
confidence: 99%
“…These researchers 259 suggest simply reversing the portion of the genome of the focal taxon under consideration 260 (e.g., the portion of the rRNA operon commonly used for molecular metabarcoding). The 261 approach ofHardwick et al 2018 was suggested for shotgun metagenomics. Notably, if such 262 a technique is used for single-locus, metabarcoding, correct-sense primer sequences must be 263 appended to the reversed sequence to ensure amplification.…”
mentioning
confidence: 99%
“…Spiked standards are commonly used in method calibration and have recently been applied to quantifying taxa in microbiome research. [19][20][21][22][23] These methods require a purified DNA sequence of known concentration from an organism not present in the sample and an estimate of the initial sample concentration to determine the amount of exogenous DNA to spike-in. Another group of anchoring methods, such as those that use flow cytometry 24 , total DNA 25 , or qPCR [26][27][28] , measure the total concentration of cells, DNA, or amplicons to transform the relative abundances to absolute numbers.…”
Section: A Quantitative Sequencing Framework For Absolute Abundance Mmentioning
confidence: 99%
“…The accuracy of the genome assembly, genome partitioning (binning) and read depth proportional to consortium makeup can then be used to confirm software accuracy. In principle, every metagenome experiment could employ in vitro positive and negative controls by "spiking" known amounts of DNA from known sources, as has been widely used for gene expression analysis [44] and increasingly for metagenomics [45][46][47] . In silico methods use selected publicly-available genome sequences.…”
Section: Positive and Negative Control Dataset Selectionmentioning
confidence: 99%